Modularized Perturbation of Alternative Splicing Across Human Cancers - Du, Yabing; Li, Shoumiao; Du, Ranran; Shi, Ni; Arai, Seiji; Chen, Sai; Wang, Aijie; Zhang, Yu; Fang, Zhaoyuan; Zhang, Tengfei; Ma, Wang (Frontiers in Genetics, 2019)
Splicing perturbation in cancers contribute to different aspects of cancer cell progression. However, the complete functional impact of cancer-associated splicing have not been fully characterized. Comprehensive large-scale studies are essential to unravel the dominant patterns of cancer-associated splicing. Here we analyzed the genome-wide splicing data in 16 cancer types with normal samples, identified differential splicing events in each cancer type. Then we took a network-based and modularized approach to reconstruct cancer-associated splicing networks, determine the module structures, and evaluate their prognosis relevance. This approach in total identified 51 splicing modules, among which 10/51 modules are related to patient survival, 8/51 are related to progression-free interval, and 5/51 are significant in both. Most of the 51 modules show significant enrichment of important biological functions, such as stem cell proliferation, cell cycle, cell growth, DNA repair, receptor or kinase signaling, and VEGF vessel development. Module-based clustering grouped cancer types according to their tissue-of-origins, consistent with previous pan-cancer studies based on integrative clustering. Interestingly, 13/51 modules are highly common across different cancer types, suggesting the existence of pan-cancer splicing perturbations. Together, modularized perturbation of splicing represents an functionally important and common mechanism across cancer types.